Fresno County Bar Association Judges' Dinner at Crossland's Barn with Bernie Witkin - Watkins, Howard::::::::: (1989)
Retired Judge Harold Thompson and Bernard E. Witkin; they and Judge Jim Paige met by happenstance at Shaver Lake's Lakewood Village Resort in the early 1970s, This led to the Fresno County Bar Association's Annual Witkin Luncheon